(untitled) (Indian Journal of Arid Horticulture, 2025)
The mandarin (Citrus reticulata Blanco) cultivar- Nagpur belongs to family rutaceae and is one of the important fruits of citrus group. Nagpur mandarin are of importance because of their pleasant flavors and refreshing taste. It is a sub acidic fruit, used for preparing commercial pectin, refreshing drinks and making cosmetics. However, the fruits are perishable in nature. During harvesting season, there is a gult in the market compelling the farmers to sell their produce at throw away prices. The fluctuation in market price can be controlled by selling the fruits in phases and this can be achieved by storing the fruits with the treatment of different chemicals to prolong the shelf life of mandarin fruits. The main objectives of different types of chemicals is to control the rate of respiration, transpiration, ripening and also other undesirable bio- chemical changes and disease infections (Naik, 1985).